Some aspects of broad-scale cloud distribution over Indian Ocean during Indian Southwest Monsoon Season (MAUSAM, 1968)
Satellite cloud information and ship data collected during the I.I.O.E. period are utilised to study the broad-scale cloud distribution over Indian Ocean during Indian southwest monsoon season, Examination of a large number of satellite observed cloud patterns over the Indian Ocean during the southwest monsoon season reveals some aspects of broad-scale cloud features. These features are looked in to in relation to the low level wind field and an attempt is made to establish a linkage between the cloud field and the wind field. Analysis of I.I.O.E. ship data collection also lends support to the conclusions derived from satellite data. Certain features of equatorial cloud distribution are also pointed out. The difference in the cloud distribution between tropical Atlantic and Pacific and tropical Indian Ocean is adduced to the differences in sea surface temperature distribution as well as geographical distribution of land and sea areas.